Innovative Low-Calorie Apple Pie Product with Natural Sweeteners as an Alternative Snack for Low-Calorie Diets - Maulidina, Isna Rizky; Tyastirin, Esti; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2025)
Healthy food innovations are urgently needed to address the rising prevalence of obesity and diabetes caused by excessive sugar consumption. Therefore, choosing healthy snacks or foods is crucial in today’s era to avoid unwanted diseases. This study aims to develop a low-calorie apple pie product with natural honey sweetener as a healthy snack alternative. The method used is a research and development model (R7D) 4D (Define, Design, Develop, Deploy). The apple pie product is formulated using apples as a source of fiber and antioxidants, and honey as a natural sweetener to replace sugar. Nutritional content calculations show that one serving of apple pie contains 84 kcal, categorizing it as a low-calorie snack. Organoleptic tests on 30 respondents indicated good acceptance, particularly in terms of taste (57% strongly liked, 33% liked), and appearance (37% strongly liked, 43% liked). Thus, this low-calorie apple pie innovation has the potential to become a diet-friendly dessert alternative that can be consumed by various groups, including diabetics, obese individuals, and those on a low-calorie diet.